Rifampin phosphotransferase is an unusual antibiotic resistance kinase - Stogios, Peter J.; Cox, Georgina; Spanogiannopoulos, Peter; Pillon, Monica C.; Waglechner, Nicholas; Skarina, Tatiana; Koteva, Kalinka; Guarné, Alba; Savchenko, Alexei; Wright, Gerard D. (Nature communications, 2016)
Rifampin (RIF) phosphotransferase (RPH) confers antibiotic resistance by conversion of RIF and ATP, to inactive phospho-RIF, AMP and P i . Here we present the crystal structure of RPH from Listeria monocytogenes (RPH- Lm ), which reveals that the enzyme is comprised of three domains: two substrate-binding domains (ATP-grasp and RIF-binding domains); and a smaller phosphate-carrying His swivel domain. Using solution small-angle X-ray scattering and mutagenesis, we reveal a mechanism where the swivel domain transits between the spatially distinct substrate-binding sites during catalysis. RPHs are previously uncharacterized dikinases that are widespread in environmental and pathogenic bacteria. These enzymes are members of a large unexplored group of bacterial enzymes with substrate affinities that have yet to be fully explored. Such an enzymatically complex mechanism of antibiotic resistance augments the spectrum of strategies used by bacteria to evade antimicrobial compounds. Antibiotic resistance is a major clinical problem that threatens to undermine our ability to control infectious diseases. Here the authors present detailed structural analysis of Rifampin phosphotransferase from Listeria monocytogenes , yielding insight on how this class of enzyme inactivates its target antibiotics.